Autonomous and sustainable air navigation technologies shaping the future of aeronautical engineering - Ribeiro Karanjikar Rae; Murashov Sutton Görür; Babiceanu Babiceanu; Sándor Sándor (Institute of Computer Science (IOCS), 2021)
Technology, regulation, operations, and environmental awareness are transforming the aviation business. This study examines aeronautical technologies, focusing on paradigm-shifting autonomous and sustainable air navigation. A multidimensional conceptual framework encompassing unmanned aerial vehicles (UAVs), electric and hybrid-electric propulsion, Urban Air Mobility (UAM), sustainable aviation fuels (SAFs), advanced avionics, AI, noise reduction technologies, and collaborative stakeholder engagement emerges from a comprehensive review of existing research. In a numerical route planning scenario, optimal route optimization reduces fuel consumption, emissions, and operational costs while meeting energy restrictions. This shows how mathematics helps solve air navigation's modern problems. A holistic, interdisciplinary strategy is needed to address the numerous, interwoven aspects of autonomous and sustainable air navigation. Technology and regulation must work together to integrate autonomous and sustainable technology. The research shows how air traffic management systems must balance safety, efficiency, and environmental stewardship. Aviation engineers, environmental specialists, regulatory authorities, lawmakers, and industry stakeholders must work together to make skies safer, more accessible, and environmentally friendly. This research helps aviation engineering enter a new era of autonomous and sustainable flight navigation. As the aviation industry moves toward this transformative horizon, it promises improved operational efficiency, environmental sustainability, and societal advancement, ushering in an age of aviation that harmonizes human aspirations with the vast sky